Goto Group's Path To Profitability: A Financial Performance Analysis 2022-2024 - Mumtaz Muzaffar; Yunieta Anny Nainggolan; Subiakto Soekarno (International Journal of Science and Environment (IJSE), 2026)
This is a case study concerning the path to profitability of the GoTo Group in 20222024. The study follows a quantitative descriptive research design and uses secondary data retrieved in reference to audited financial statements, annual reports, and presentations made to investors, to make an integrated financial model to indicate the key drivers behind the improvement in Adjusted EBITDA. Results show that GoTo achieved a significant profitability turnaround with Adjusted EBITDA improving by IDR 16.34 trillion from negative IDR 16.01 trillion (2022) to positive IDR 0.33 trillion (2024). Three reinforcing levers drove this improvement: (1) monetization uplift with net take-rate rising from 1.85% to 2.95%, (2) subsidy rationalization with promotions declining from 2.97% to 0.53% of Core GTV, and (3) fixed cost efficiency maintained at 44.84% of net revenue. Scenario analysis demonstrates that profitability sustainability exists within a narrow operating corridor. The study establishes quantified profitability guardrails: promotion intensity ≤0.59% of Core GTV, net take-rate ≥2.84%, and fixed opex ≤46.91% of net revenue. This study recommends implementing guardrail-based governance to maintain profitability while growing Core GTV without returning to subsidy-dependent growth.